Comparative In-vitro Anthelmintic Activity of the Latex of Ficus religinosa, Ficus elastica and Ficus bengalensis - Ramya Devi, B.N. Vedha Hari*, P. Saravana Kumar, D. (Journal of Phytology, 2011)
The World Health Organization estimates that a staggering two billion people harbor parasitic worm infections. Parasitic worms also infect livestock and crops, affecting food production with a resultant economic impact. The three plants present in the study are Ficus religinosa, Ficus elastica and Ficus bengalensis. They belong to the family Moraceae and are traditionally used for various diseases. Our aim was to investigate the anthelmintic activity of the latex of three plants. The latex of the plants was taken for anthelmintic activity against Indian earthworm Pheritima posthuma. Various species of the ficus latex was tested and results were expressed in terms of time for paralysis and time for death of worms. Metronidazole (10mg/ml) was used as a reference standard and distilled water as a control group. From the results of this study found that the three plants possess anthelmintic activity but Ficus religinosa shows more activities compared to others. Key words: F.religinosa, F.elastica, F.bengalensis, Metronidazole, Anthelmintic activity, latex <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">B.N. Vedha Hari et al. Comparative In-vitro Anthelmintic Activity of the Latex of Ficus religinosa, Ficus elastica and Ficus bengalensis. J Phytol 3/3 (2011) 26-30.